The relevancy of privileged wills of members of armed forces: enhancing the role of the armed forces council - Hussain, Faridah; Mohd Kamal, Mohd Hisham; Halim, Akmal Hidayah; Ahmad Bustami, Tajul Aris (ScitePress, 2020)
This paper aims to highlight the relevancy of privileged wills and the power of the Armed Forces Council to come up with the relevant policy to enable members of the regular forces of Malaysia to execute privileged wills in Malaysia. Recognising the dangerous global nature of duty faced by members of the armed forces, many countries have granted them the exclusive right of making privileged wills including making a written will with no witnesses or oral will whose contents could be proved by only one witness. The law provides that the members of the armed forces are free to make a will informally on a temporary basis while on actual military service or while being at sea. For this purpose, this paper adopts a qualitative research methodology as it provides a deeper understanding relating to privileged wills in Malaysia. This paper concludes that the law relating to privileged wills is still relevant and important as a way forward in the 21st century. Their position of preparedness in duties for the preservation of life and property makes it necessary for them to be privileged personnel. The Armed Forces Council should exercise its power under the Federal Constitution